Ratcheting and constitutive patterns of rate-form defined in Preferred Reference Frames - Guelin, P.; Nowacki, W.K.; Quereyron, D.; Tourabi, A. (Archives of Mechanics, 1999)
A pattern of Rate Form allowing the modelling of the thermomechanical features of the cyclic plasticity has proved to be effective in order to take into account various isotropic behaviours, ranging from those of granular media exhibiting isotropic-deviatoric coupling effects, to those distinguished by shape memory effects or ferrohysteresis ([1] to [8]). Under its basic form, of pure hysteresis type, this discrete memory pattern is able, by definition of a formalism brought into play in the fixed frame and in the A.A. Illushin space of stress, to describe the behaviour involving perfectly closed cycles. Owing to this fact, it is also unable, in its basic form, to take into account second order effects such as those of multiaxial effects of ratchet type. In order to introduce a well founded and straightforward approach to the continuum thermo-mechanics of the isotropic solid-like inelastic behaviours, including rate-independent and hardening-independent second order tensorial coupling effects of ratchet type, a new approach is introduced. It is founded on the following assumptions: firstly, the formalism of the initial pattern is not modified, maintaining its role in the A.A. Iliushin spaces of stress and strain (of power and geometry); secondly, the unaltered initial formalism is no longer brought into play in the fixed frame and works now in the Preferred Reference Frame (PRF); thirdly, the definition of this PRF is basically thermomechanical and may be dependent on a mesoscale of Nél-Krumhansl type. The formalism of the general multiaxial isotropic case is introduced and the approach is shown to be straightforward even when the pattern is (easily) generalized to the viscoela.stoplastic case. It is shown that the usual multiaxial effect of ratchet type obtained through cyclic torsion is not necessarily hardening-dependent and is existing under zero axial load, in accordance with experimental evidence.